Validation of the Iranian/Persian version of the perceived therapeutic efficacy scale for type 2 diabetes - Azami, Golnaz; Lam, Soh Kim; Shariff-Ghazali, Sazlina; Md. Said, Salmiah; Aazami, Sanaz; Mozafari, Mosayeb; Taghinejad, Hamid (Academy of Medical Sciences of I.R. Iran, 2018)
Background: The theory if self-efficacy is the central concept of social cognitive theory with emphasis on the constructs of efficacy expectation, outcome expectation. Efficacy expectation is defined as the person’s confidence to carry out a specific behavior. Outcome expectation is beliefs that carrying out a specific behavior will lead to a specific outcome. While the benefit of measuring outcome expectations has been established, there has been no large scale within the Iranian context. The purpose of this study is to examine the reliability-validity of the Persian version of the Perceived Therapeutic Efficacy Scale (PTES).